Terawatt-class femtosecond long-wave infrared laser - Pogorelsky, Igor. V.; Polyanskiy, Mikhail N.; Babzien, Marcus; Simmonds, Andrew; Palmer, Mark A. (Frontiers in Physics, 2024)
We utilized a nonlinear post-compression technique to generate 675-fs, 9.2-μm CO2 laser pulses with a peak power of 1.6 TW. This achievement represents the highest peak power ever attained in the femtosecond pulse format within the long-wave infrared (LWIR) spectral range. The successful implementation of this post-compression technique opens avenues for the development of few-cycle, multi-terawatt 9-10 μm lasers, crucial for applications currently relying on near-infrared (NIR) solidstate lasers, and which stand to benefit from the scaling of laser wavelengths into the LWIR region.